1999
DOI: 10.1017/s0007114599001646
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the regression of atherosclerosis in the hamster by dietary lipids: comparison of coconut oil and olive oil

Abstract: The Golden Syrian hamster (Mesocricetus auratus) has been shown to be a useful model of both human lipoprotein metabolism and the development of atherosclerosis. We report the effects of dietary lipids on the progression and regression of atherosclerosis in this model. In the first study, hamsters fed on coconut oil (150 g/kg diet) and cholesterol (30 g/kg diet) developed lipid-rich lesions in the ascending aorta (0⋅28 (SD 0⋅14) mm 2 ) and aortic arch (0⋅01 (SD 0⋅01) mm 2 ) after 4 weeks that continued to prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 30 publications
3
31
1
Order By: Relevance
“…The positive close relationship between the triglyceridemia and the severity of lipid deposition in the aorta of rabbits was already reported in hamsters (Mangiapane et al, 1999) and is in accordance with the fact that hypertriglyceridemia is an independent risk factor of atherosclerosis in human (Hennig et al, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…The positive close relationship between the triglyceridemia and the severity of lipid deposition in the aorta of rabbits was already reported in hamsters (Mangiapane et al, 1999) and is in accordance with the fact that hypertriglyceridemia is an independent risk factor of atherosclerosis in human (Hennig et al, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…28 The regression of fatty streaks was also found in another study 29 with a low-fat, low-cholesterol diet with or without supplementation of lovastatin. In a recent study, 30 the effect of coconut oil versus olive oil on regression of lesions in the ascending aorta and aortic arch was compared after 8 or 16 weeks. In the ascending aorta, coconut oil increased the extent of lesions, whereas with olive oil, no regression occurred up to 16 weeks.…”
Section: Hamstersmentioning
confidence: 99%
“…Different results were reported for aortic arch, in which both coconut oil and especially olive oil enhanced regression. 30 …”
Section: Hamstersmentioning
confidence: 99%
“…It has also proven to be a useful model in studying pharmacological (Kowala et al 1991(Kowala et al , 1993Foxall et al 1992;Otto et al 1995;Nicolosi et al 1998a;Pitman et al 1998) and nutritional influences on the development of atherosclerosis (Parker et al 1995;Kahlon et al 1996;Nicolosi et al 1997Nicolosi et al , 1998bXu et al 1998;Mangiapane et al 1999). Previous studies in our laboratory (Mangiapane et al 1999) showed that one strain of hamster (dominant spot normal inbred, DSNI) required high levels of dietary cholesterol (30 g/kg diet) to induce aortic lesions. This is in agreement with earlier findings of Nistor et al (1987).…”
mentioning
confidence: 99%